Migration, Trafficking, and the Greek Economy: A comment on ‘the trafficker next-door’ - Papanicolaou, Georgios; Antonopoulos, Georgios (Anti-Trafficking Review, 2022)
This article interrogates the manifestations and implications of the intertwining of migration policies and the global prohibition regime against human trafficking in Greece. In a dramatic reversal of long historical patterns, post-cold war Greece became a migration destination country, receiving a large number of migrants. While Greece’s policies approached the phenomenon as an administrative embarrassment, migrant populations joined the country’s productive structures and arguably made a decisive contribution to the country’s economic boom. The restrictive regime on migration took a further twist as Greece aligned with the global prohibition regime established with the 2000 UNTOC and Trafficking Protocol. The combination of migration and anti-trafficking policies has engendered a punitive overreach that severely disadvantaged migrant populations in Greece. Drawing on our research, we reflect on several common cases where the precarious status of the migrant meshes potentially with the punitive effects of anti-trafficking policies. We argue that the obfuscation of extremely harmful conditions typically experienced by migrants involved in Greece’s economic structures has been the most distinctive effect of the intertwining of migration and anti-trafficking policies.